2017
DOI: 10.1111/eea.12618
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interruption of over‐flooding releases of transgenic mosquitoes over wild population ofAedes aegypti: two case studies in Brazil

Abstract: The number of mosquito populations resistant to insecticides is increasing along with the reemerging of vector-borne diseases. New technologies are under evaluation to complement the strategies used against these mosquitoes. Transgenic mosquitoes are one approach that some countries are considering and they are being evaluated to control the wild population. Although they have achieved success in population suppression of Aedes aegypti (L.) (Diptera: Culicidae), these studies have not demonstrated what the out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 56 publications
0
31
0
1
Order By: Relevance
“…Evidence to support these conclusions can be found when exploring recent important articles. We selected (non-systematically) 12 relevant articles published since March 2016 until now [22][23][24][25][26][27][28][29][30][31][32]. Critical successful evidence was reported, mainly field-based: (i) first stable transgenic CRISPR/cas9 aegypti-mosquitoes strain [23]; (ii) transgenic Anopheles population collapse in semifield using CRISPR/Cas9 [19]; (iii) near elimination of field mosquitoes after release of irradiated and Wolbachia-infected mosquitoes [24]; (iv) higher virus blockage of Wolbachia-infected fieldreared mosquitoes [25]; (v) wolbachia-mediated pathogen inhibition for ZIKV and ZIKV/DENV co-infection [26]; and (vi) released Wolbachia-aegypti stable over 12 months and 28 months at some sites, and reduced human dengue incidence [27,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence to support these conclusions can be found when exploring recent important articles. We selected (non-systematically) 12 relevant articles published since March 2016 until now [22][23][24][25][26][27][28][29][30][31][32]. Critical successful evidence was reported, mainly field-based: (i) first stable transgenic CRISPR/cas9 aegypti-mosquitoes strain [23]; (ii) transgenic Anopheles population collapse in semifield using CRISPR/Cas9 [19]; (iii) near elimination of field mosquitoes after release of irradiated and Wolbachia-infected mosquitoes [24]; (iv) higher virus blockage of Wolbachia-infected fieldreared mosquitoes [25]; (v) wolbachia-mediated pathogen inhibition for ZIKV and ZIKV/DENV co-infection [26]; and (vi) released Wolbachia-aegypti stable over 12 months and 28 months at some sites, and reduced human dengue incidence [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested the need to release prohibitively large number of insects (100-102). To overcome that, two solutions were reported: releases in a ratio of 95% male mosquitoes (requiring a mass rear capacity) (11) or the introduction of insecticide resistance genes along with Wolbachia in the host insect, combined with a pre-release intervention to reduce (adult) insect vector numbers (29), (3). The unintended increase of the insect population after the release of the modified insects (reversal outcomes) was estimated by computational modelling studies (103), some of them based on field data of wMelPopaegypti (100) and of superinfected Aedes albopictus (93).…”
Section: Releasementioning
confidence: 99%
“…Transgenic Ae. aegypti males possessing a dominant lethal system have been released in multiple locations where they have reduced population sizes, at least in the short term [6][7][8][9]. When these males mate with wild females, most offspring die before reaching the late pupal stage, though a low proportion can emerge as functional adults [10] and may persist for months after releases cease [9].…”
Section: Introductionmentioning
confidence: 99%
“…Garziera et al. () also presented data on a transgenic dipteran strain for SIT use, the well‐known disease vector mosquito Aedes aegypti (L.) (Diptera: Culicidae). They conclude that regular release is necessary for transgenic Ae.…”
mentioning
confidence: 99%
“…This work is the first to present data on transgenic medflies, and clearly shows that more work is needed to fully assess their effectiveness under field conditions. Garziera et al (2017) also presented data on a transgenic dipteran strain for SIT use, the well-known disease vector mosquito Aedes aegypti (L.) (Diptera: Culicidae). They conclude that regular release is necessary for transgenic Ae.…”
mentioning
confidence: 99%